Effect of ethanol extract of myrmecodia pendens on TGF-?1 expression and osteoblast cells after tooth extraction (experimental research on cavia cobaya) - Efa Ismardianita; Ellyza Nasrul; Yanwirasti Yanwirasti; Mieke Hemiawati (DiscoverSys Inc., 2017)
Objective: Myrmecodia pendens is often used as a traditional medicine to treat various disease. A previous study, ethanol extract of sarang semut plant (Hypnophytum furmicarum jack) 4.65 mg was effective in fastening establishment of socket granulation tissue after tooth extraction, the Myrmecodia pendens 3% too fasten healing soft tissue of wound after tooth extraction. The aim of this study to determine the effect of ethanol extract of Myrmecodia pendens to the expression of TGF-Î²1, and the number of osteoblasts after tooth extraction.Material and Methods: this study using 24 male marmoots were divided into 2 groups. The entire groups had extract done 1st left incisor mandibula, into the socket control group applied 0,1 ml of 0.5% CMC and treatment group was given 0,1 ml of ethanol extract Myrmecodia pendens 10% dissolved with CMC 0.5%. On day 3,7,14 and 21, marmoots were decapitated and histopathologic preparations then observed the expression of TGF-Î²1, and the number of osteoblast cell. Data analyzed by Kruskall-wallis test with probability p<0.05 and Mann-Whitney to determine differences in effectiveness between variables.Results: Based on the Kruskal-wallis test, there is a significant difference the TGF-Î²1 expression and the number of osteoblast cell which had giving ethanol extract of Myrmecodia pendens between of control group and group treatment (p<0.05), further test with Mann-Whitney for TGF-Î²1 with days of observation shown a significant difference meanwhile osteoblast with days of observation showed no significant difference.Conclusion: the ethanol extract Myrmecodia pendans can assist the wound healing process after tooth extraction by increasing the expression ofÂ TGF-Î²1, and osteoblast cells number